Pengaruh Locus of Control terhadap Dysfunctional Audit Behavior: Religious Control sebagai Pemoderasi - Prasetio, Febrina Viryani; Handojo, Irwanto; Ghazi, Muhammad (Media Bisnis, 2023)
The purpose of this study is to obtain empirical evidence about whether locus of control, professional commitment, time budget pressure, client importance, turnover intention, and personality type (type A) has an influence on dysfunctional audit behavior moderated by religious control on the influence of locus of control and professional commitment on dysfunctional audit behavior. The population in this study are auditors who work in public accounting firms in Indonesia. The sample selection technique is purposive sampling. Based on the sample selection criteria, the number of samples collected were 86 auditors. Those data are analyzed using multiple linear regressions analysis. The result of this study shows that locus of control has a positive effect on dysfunctional audit behavior. It means that the higher the locus of control, the higher the probability of dysfunctional audit behavior. Auditors tend to perform dysfunctional audit behavior when they face pressure in doing their job. The pressure can come from time, superiors, supervisors, or audit managers which are external factors. Professional commitment, time budget pressure, client importance, turnover intention, locus of control moderated by religious control, and professional commitment moderated by religious control do not effect dysfunctional audit behavior. This study also showed that religious control does not moderate the relationship between locus of control and professional commitment with dysfunctional audit behavior.